La organización comunitaria para el desarrollo del ecoturismo en la represa Tahuín del cantón Arenillas, año 2013. - Correa Montoya, Rita Katherine (2014)
The basis of social work is to guide individuals, groups and communities in problem situations that occur in everyday life , from this perspective the present research develops entitled : COMMUNITY ORGANIZATION FOR DEVELOPMENT OF ECOTOURISM IN THE DAM Tahuín CANTON ARENILLAS , 2013. The proceeds from the premise that empowering a community to participate in activities that benefit socio-economic development while respecting the environment according to the principles of Good Living.